1995
DOI: 10.1037/0021-843x.104.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy for social facilitation from drinking: The divergent paths of high-expectancy and low-expectancy adolescents.

Abstract: Using a 3-wave longitudinal design, adolescents were studied over a 2-year period during which many first began to drink. Covariance structure modeling showed that teens' expectancy for social facilitation from alcohol and their drinking experience influenced each other in a reciprocal, positive feedback fashion: the greater the expectancy endorsement, the higher subsequent drinking levels, and the higher the drinking levels, the greater the subsequent expectancy endorsement. This model fit the data quite well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
278
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(297 citation statements)
references
References 37 publications
14
278
3
2
Order By: Relevance
“…Both expectancies for not drinking and perceptions of peer drinking were associated with initiation of drinking behavior in male and female students at Time 2, and this effect was particularly strong for expectancies for not drinking. There has been consistent support for the powerful predictive value of alcohol-use expectancies for drinking initiation, intensity, and problems related to drinking (e.g., Barnow et al, 2004;Brown et al, 2001;Meier et al, 2007;Smith et al, 1995), and the current study extends this impact to adolescents' beliefs about the consequences of not drinking. Recent research has demonstrated that expectancies for not drinking also are related to the intensity of drinking (Bekman et al, in press) and attempts to quit or reduce drinking (Metrik et al, 2004), and they partially mediate the relationship between sensation seeking and drinking intensity (Bekman et al, in press).…”
Section: Discussionmentioning
confidence: 74%
“…Both expectancies for not drinking and perceptions of peer drinking were associated with initiation of drinking behavior in male and female students at Time 2, and this effect was particularly strong for expectancies for not drinking. There has been consistent support for the powerful predictive value of alcohol-use expectancies for drinking initiation, intensity, and problems related to drinking (e.g., Barnow et al, 2004;Brown et al, 2001;Meier et al, 2007;Smith et al, 1995), and the current study extends this impact to adolescents' beliefs about the consequences of not drinking. Recent research has demonstrated that expectancies for not drinking also are related to the intensity of drinking (Bekman et al, in press) and attempts to quit or reduce drinking (Metrik et al, 2004), and they partially mediate the relationship between sensation seeking and drinking intensity (Bekman et al, in press).…”
Section: Discussionmentioning
confidence: 74%
“…Individuals high in positive and negative urgency, facets of impulsivity, have also been found to act more in line with their implicit alcohol cognitions than individuals with lower levels of these traits (Burton et al, 2012). Research has shown that explicit expectancies and alcohol use reciprocally infl uence one another (e.g., Smith et al, 1995). However, because this association is potentially reduced for individuals with lower executive control, expectancy development may be attenuated in ADHD and result in lower mean levels of explicit alcohol expectancies.…”
Section: Alcohol Expectanciesmentioning
confidence: 99%
“…Previous observations of children and adolescents suggest there is a gradual shift from negative (aversive) to positive (rewarding) alcohol expectancies as one becomes older [11-14]. Etiologic and treatment researchers are increasingly finding that alcohol expectancy has several dimensions and plays a significant role in the progression of initiation, heavy use, abuse or dependence, and relapse among adolescent and adult populations [15-18]; generally, heavy or problematic drinkers are more likely to endorse higher positive alcohol expectancy. To illustrate, Christiansen and colleagues reported that high scores in two dimensions (i.e., "Alcohol can enhance social behaviors" and "Alcohol improves cognitive and motor functions") significantly predicted the risk of increased consumption (i.e., quantity/frequency) and problem drinking a year later among junior high school students in Detroit [19].…”
Section: Introductionmentioning
confidence: 99%